The Importance оf Small and Medium Enterprises in the Economic Development of Eastern Europe - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Хмарська, Ірина Анатоліївна; Хмарська, І. А.; Хмарская, Ирина Анатольевна; Khmarska, Iryna A.; Ткаченко, Тетяна Валентинівна; Ткаченко, Т. В.; Ткаченко, Татьяна Валентиновна; et al. (WSEAS, 2021)
An important engine of economic development of the country is the development of small and medium enterprises. At the same time, small and medium-sized businesses, being elements of the economic system, have a significant impact on the overall economic growth of the country. Thus, there is a mutual influence of economic units on the economy as a whole. The purpose of the article is to study the impact of small and medium-sized enterprises on the gross domestic product on the example of Eastern European countries. Methods: analysis, description, observation, comparison, generalization, induction, deduction, grouping, systematization, tabular and graphical representation. Results: The level of ease of doing business in Eastern Europe was analyzed according to the Ease of doing business ranking and it was found that the Czech Republic and Poland are among the 40 countries in Eastern Europe ranked 40th and 41st out of 190 possible. It is established that the subjects of small (including microenterprises) and medium-sized enterprises belonging to the non-financial sector, in the structure of all enterprises of the non-financial sector of each of the studied countries occupy more than 90%. It was found that a significant share in the structure of small and medium enterprises in Eastern Europe is occupied by microenterprises, while the share of medium-sized enterprises is the lowest. The results of regression analysis to determine the impact of small and medium enterprises on the economic growth of countries obtained by establishing the dependence of GDP on Turnover of the non-financial business economy by size class of employment. Revealed a high dependence of GDP Turnover of the non-financial business economy by size class of employment in all surveyed countries in Eastern Europe.

Важливим двигуном економічного розвитку країни є розвиток малого та середнього підприємництва. При цьому малий і середній бізнес, будучи елементами економічної системи, справляє значний вплив на загальне економічне зростання країни. Таким чином, відбувається взаємний вплив господарських одиниць на економіку в цілому. Метою статті є дослідження впливу малих та середніх підприємств на валовий внутрішній продукт на прикладі країн Східної Європи. Методи: аналіз, опис, спостереження, порівняння, узагальнення, індукція, дедукція, групування, систематизація, табличне та графічне зображення. Результати: Рівень легкості ведення бізнесу в Східній Європі було проаналізовано відповідно до рейтингу «Легкість ведення бізнесу», і було виявлено, що Чехія та Польща входять до 40 країн Східної Європи, які займають 40 та 41 місце з 190 можливих. Встановлено, що суб’єкти малих (у тому числі мікропідприємств) та середніх підприємств, що належать до нефінансового сектору, у структурі всіх підприємств нефінансового сектору кожної з досліджуваних країн займають понад 90%. Встановлено, що значну частку в структурі малих і середніх підприємств у Східній Європі займають мікропідприємства, тоді як частка середніх підприємств є найнижчою. Результати регресійного аналізу для визначення впливу малих і середніх підприємств на економічне зростання країн отримано шляхом встановлення залежності ВВП від товарообігу економіки нефінансового бізнесу за розмірним класом зайнятості. Виявлено високу залежність обороту ВВП економіки нефінансового бізнесу від класу зайнятості в усіх досліджуваних країнах Східної Європи.
Petrunenko I. The Importance оf Small and Medium Enterprises in the Economic Development of Eastern Europe / I. Petrunenko, I. Khmarska, T. Tkachenko, H. Koptieva, V. Komandrovska // Transactions on Environment and Development. - Vol. 17. - WSEAS, 2021. - P. 898–910.
Keywords: small and medium enterprises; micro-enterprises; non-financial sector; economic growth; gross domestic product; малі та середні підприємства; мікропідприємства; нефінансовий сектор; економічне зростання; валовий внутрішній продукт; Research Subject Categories::SOCIAL SCIENCES::Business and economics